Analysis Of The Effect Of Financial Incentives On The Affective Commitment Of Civil Servants - Nuzulul Rochman; Ira Irawati; Rusliandy Rusliandy (Jurnal Ilmu Sosial Mamangan, 2024)
Financial incentives can increase affective commitment which ultimately improves organizational performance. This research is intended to analyze the influence of financial incentives on the affective commitment of civil servants within the Bogor Regency Government. The method used is a quantitative approach with data analysis using SEM PLS on 365 sample people from a total population of 4,210 people. The research results concluded that financial incentives had a positive effect on employee affective commitment. If financial incentives are increased, it will increase employee affective commitment. Recommendations from the research are the need to improve financial incentives by paying attention to reimbursement for telephone costs, and improve affective commitment through indicators of the desire to stay in the organization and feelings of belonging to the organization.